University Autonomy Decline Causes, Responses, and Implications for Academic Freedom - Roberts Lyer, Kirsten (Routledge Research in Higher Education, 2023)
This book provides empirically grounded insights into the causes, trajectories, and effects of a severe decline in university autonomy and the relationship to other dimensions of academic freedom by comparing in-depth country studies and evidence from a new global timeseries dataset. Drawing attention to ongoing discussions on standards for monitoring and assessment of academic freedom at regional and international organizations, this book identifies a need for clearer standards on academic freedom and a human rights-based definition of university autonomy. Further, the book calls for accompanying international oversight and the inclusion of criteria related to academic freedom in international university rankings. Five expert-authored case studies on academic freedom from diverse nations (Bangladesh, Mozambique, India, Poland, and Turkey) are included in the volume. Drawing on both qualitative and quantitative evidence, the book offers a unique and timely contribution to the field and will be of great interest to scholars, researchers, and students in the fields of higher education, human rights, political science and public policy.